العوامل المدرسية و علاقتها بالتحصيل الدراسي - قناني، صفاء (جامعة الوادي university of Eloued, 2017)
Résumé: The aim of this study was to uncover the relationship between the school factors and the student's scholastic achievement. To this presentation, we relied on the following questions: - What is the relationship between school factors and student achievement? A number of sub-questions have emerged from this question: - What is the relationship of good educational behavior of the professor to the student's academic achievement? - What is the relationship between the density of the program and the academic achievement? - What is the peer group's relationship to school achievement? To answer the following questions, we have developed hypotheses: - Good educational behavior leads to improving the level of student achievement. - The intensity of the program leads to low level of academic achievement of the student. - The school peer group contributes to the low level of student achievement. The nature of the study required the analytical descriptive approach, which is one of the most widely used methods in the social and human sciences, with the use of a set of research techniques to obtain the field data (the form), which was applied to the sample of the study and contained 35 items representing the society of the study in secondary school students The study sample was estimated at 120 students and the study reached the following results: - The first hypothesis: The good educational behavior of the professor lead to improve the level of educational achievement of the student. - Check the second hypothesis: the course leads to low level of educational achievement of the student. - The third hypothesis: The school peer group contributes to the low level of student achievement.
دراسة ميدانية بثانويتي: عيدة عبد الرزاق وبوصبيع صالح عبد المجيد بولاية الوادي
مذكرة ماستر علوم اجتماعية تخصص علم اجتماع التربية
Keywords: التحصيل الدراسي، المدرسة; résultat scolaire; Academic achievement